(untitled) - Abegglen, James C. (New York, 1958)
This book introduce about industry in ASIA: the case of Japan. The critical differience: a lifetime commitment. The rẻcuitment of personnel...
Keywords: Factory system,Industrial relations,Hệ thống nhà máy,Quan hệ công nghiệp; Japan,Japan,Nhật Bản,Nhật Bản